The complete mitochondrial genome sequence of Aulacophora indica - Jiang, Weiling (Mitochondrial DNA B Resour, 2019)
Aulacophora indica has been intensively studied since it can cause serious damage to cucurbits. Here, we reported the complete mitochondrial genome of A. indica for the first time. The mitochondrial genome is 15,730 bp in length and contained 13 protein-coding genes (PCGs), 2 rRNAs, 22 tRNAs, and an AT-rich control region. Phylogenetic tree indicated that A. indica is more closely related to Aulacophora lewisii than other Galerucinae beetles.